The Influence of Alkali Cations on the Performance of Pt Electrodes in Kolbe Electrolysis of Acetic Acid - Talal Ashraf; Prof. Bastian Timo Mei; Prof. Guido Mul (ChemElectroChem)
Abstract Electrochemical decarboxylation of carboxylic acids is considered a sustainable method to improve the quality of pyrolysis oil. In this study, we assess the effect of monovalent alkali cations (of the acetates) on the performance of Pt electrodes in acid decarboxylation and the competing OER, using various electrochemical methods. We reveal a strong cation dependence generally following the trend Li+<Na+<K+~Cs+ within a large pH range. Using rotating ring disc electrode measurements, we highlight the strong contribution of the oxygen evolution reaction particularly for electrolytes containing Li+ and Na+ which decreases the selectivity for Kolbe oxidation. In addition, the faradaic efficiency (FE) towards methanol ranges between 16 % (for Li+) and 29 % (for Cs+) at high solution pH (9 or 12). The observed trends are generally explained by a cation‐dependent interfacial pH and surface coverage of acetate, both lowest for Li. This is evident from differences in charge transfer resistance determined by impedance measurements and local pH measurements. Additionally, enhanced dissolution of Pt by Li+ is also proposed. This work highlights that K+ and Cs+ cations favor FE for electrochemical Kolbe oxidation, at relatively low current densities.